Clinical factors stratifying the risk of tumor upgrading to high-grade disease in low-risk prostate cancer. Issue 2 (March 2018) - Porcaro, Antonio B.; Siracusano, Salvatore; Luyk, Nicolò de; Corsi, Paolo; Sebben, Marco; Tafuri, Alessandro; Processali, Tania; Cerasuolo, Mattia; Mattevi, Daniele; Inverardi, Davide; Cerruto, Maria A.; Brunelli, Matteo; et al.
Purpose: To identify clinical factors stratifying the risk of tumor upgrading to increasing patterns of the tumor grading system in low-risk prostate cancer (PCa). Methods: We evaluated the records of 438 patients who underwent radical prostatectomy. Associations between clinical factors and tumor upgrading were assessed by the univariate and multivariate multinomial logistic regression model. Results: Low-risk PCa included 170 cases (38.8%) and tumor upgrading was detected in 111 patients (65.3%): 72 (42.4%) had pathology Gleason pattern (pGP) 3 + 4, 27 (15.9%) pGP 4 + 3, and 12 (7.1%) pGP 4 + 4. Prostate- specific antigen (PSA) and proportion of positive cores (P+) were independent predictors of upgrading to high-risk disease. These factors also stratified the risk of tumor upgrading to the increasing patterns of the tumor grading system. The model allowed the identification of pGP 4 + 4. The main difference between high-risk PCa and other upgraded tumors related to PSA load (odds ratio 2.4) that associated with high volume disease in the specimen. Conclusions: Low-risk PCa is a heterogeneous population with significant rates of tumor upgrading. Significant clinical predictors stratifying the risk of tumor upgrading to increasing patterns of the grading system included PSA and P+. These factors allowed the identification of the subset hiding high-grade disease requiring further investigations before delivering active treatments.